(untitled) (Research, Society and Development, 2020)
Social Technology is a solution to a problem in a given locality where the population is involved in the development of this solution. These technologies have been applied in various areas, especially sanitation, environment and energy. In this context, the objective of this study was to develop jointly with the community of Vila Santíssima Trindade, in Santa Isabel do Pará, a water supply system powered by photovoltaic energy. In order for the community to be part of the process of elaboration of this, it would be trained on the importance of social technologies for sanitation, health and environment. However, from the pandemic events, the stages of social interaction had to be suspended and data collection was restricted to observational research and web interviews with the representative of the community residents’ association. However, there was a need to hold a meeting with the community in order to define some points of the project. In this meeting, the community participated in defining the locations of the underground spring and the distribution reservoir. In addition, it has agreed to raise funds for the purchase of the photovoltaic system, so that it has proposed to draw up a raffle ticket for an internet system for rural locations. In this way, the community was empowered to seek a solution to its problem, even in the midst of a pandemic. Therefore, it is possible to affirm that the community was successful in what concerns the popular participation in the development of a solution, consequently succeeding in relation to social technology.